MODAL SOSIAL DAN KEBERLANJUTAN PEMANFAATAN LAHAN HUTAN UNTUK PENGELOLAAN DUSUNG - Marthina Tjoa; George S J Tomatala; Iskar Iskar (Pattimura Proceeding, 2022)
The use of forest land by the community in the form of dusung is based on the prevailing social system. the social system of the community is influenced by the rules, norms and values that have been internalized in the life of indigenous peoples. The rules of customary norms and values have regulated community interactions that support the strength of social capital. This study aims to determine the role of social capital and the sustainability of dusung management in Maluku. The approach used is a participatory follow-up study (PAR). The results of the study show that various facts and concepts about social and cognitive structures are important factors in revealing the forms of social capital that exist in the community to realize dusung management at the individual, group and village level as a whole. Social capital has played a role in helping the development of community capacity in the sustainability of dusung management, because of the level of security and certainty of a more secure social action